The Mormon vanguard brigade of 1847 : Norton Jacob's record - Jacob, Norton, 1804-1879 (Book collections on Project MUSE., 2005)
The diary published here begins in 1844, the year of Mormon church founder Joseph Smith's murder. It continues through the crisis events that followed, including the Mormons' flight from Nauvoo and the beginnings of mass migration to Utah. After the apex of 1847, the arc of the narrative moves through accounts of Norton Jacob's return to Nauvoo late that year and of the much larger Mormon emigration in 1848. It reaches denouement in a short record of his first years in Salt Lake Valley.